2021
DOI: 10.1071/cp21369
|View full text |Cite
|
Sign up to set email alerts
|

Fungicide sensitivity and resistance in the blackleg fungus,

Abstract: Fungicide use has become a fundamental part of many crop protection systems around the world, including to control blackleg disease on canola (Brassica napus L.). In Australia, most canola growers routinely apply at least one fungicide, and potentially multiple fungicides with different modes of action, in a single growing season. There is evidence for the emergence of fungicide resistance in Leptosphaeria maculans, the causal agent of blackleg disease, to the demethylation inhibitor (DMI) class of fungicides … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 29 publications
4
11
0
Order By: Relevance
“…LepR1 can also be an significant source of blackleg resistance for the cultivars in Australia, which has virulent L. maculans population causing the breakdown of the cultivars containing R gene like LepR3 and ineffectiveness of R genes like Rlm1 and Rlm3 ( Li et al., 2005 ; Van de Wouw et al., 2014 ; Van de Wouw et al., 2021 ). Other studies have also shown that cultivars with LepR1 are more effective than those with R genes Rlm1, Rlm3, Rlm4 , and LepR3 ( Alnajar et al., 2022 ; Rashid et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…LepR1 can also be an significant source of blackleg resistance for the cultivars in Australia, which has virulent L. maculans population causing the breakdown of the cultivars containing R gene like LepR3 and ineffectiveness of R genes like Rlm1 and Rlm3 ( Li et al., 2005 ; Van de Wouw et al., 2014 ; Van de Wouw et al., 2021 ). Other studies have also shown that cultivars with LepR1 are more effective than those with R genes Rlm1, Rlm3, Rlm4 , and LepR3 ( Alnajar et al., 2022 ; Rashid et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, DMIs are categorized as medium-risk fungicides by FRAC. There have only been a few studies on resistance to fungicides, which have been mostly focused on L. maculans sensitivity to strobilurins (quinone outside inhibitor; QoI) [32,33] and other DMI fungicides [20][21][22]24,34]. However, similar to other phytopathogenic fungi [35][36][37][38][39][40][41], resistance to DMI fungicides in L. maculans has also been documented [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…This made it difficult to determine the sensitivity of the isolates to these fungicides based on mean EC 50 alone. However, this is not surprising because none of the other studies were based on the sensitivity of L. maculans isolates to tetraconazole, metconazole, and prochloraz, but rather to flusilazole, fluquinconazole, prothioconazole, and tebuconazole [20][21][22]24,34]. Resistance to DMI fungicides is quantitative, meaning it develops in a stepwise gradual progression [18].…”
Section: Discussionmentioning
confidence: 99%
“…Current fungal disease management strategies are largely reliant on the use of chemical fungicides, host resistance and cultural practices such as crop rotation. However, fungicide usage can lead to the target species developing resistance and synthetic fungicides can be harmful to humans, beneficial organisms and the broader environment (Van de Wouw et al, 2021). Alarmingly, fungicide‐resistant fungal strains have been reported for every major class of antifungals used in agriculture (Fisher et al, 2018).…”
Section: Introductionmentioning
confidence: 99%